Enhancing Astronomical Literacy In Maritime Navigation: Impact Of Social Media and Citizen Science - Marudut Bernadtua Simanjuntak; Chanra Purnama (Pusat riset dan Inovasi Nasional, 2024)
This study investigates the influence of social media and citizen science initiatives on astronomical literacy and its application in maritime navigation among transportation cadets. Through qualitative research methods, including interviews and observational studies, the perceptions and practices of 40 cadets at a transportation institute in Jakarta were explored. The findings reveal that social media platforms play a significant role in enhancing navigational knowledge and skills among cadets, providing access to diverse educational resources and fostering engagement with astronomical content. Similarly, participation in citizen science projects positively impacts astronomical literacy, offering hands-on learning experiences that reinforce theoretical knowledge. Moreover, the research highlights the importance of promoting cultural competence in maritime education to prepare cadets for navigating in multicultural environments. By aligning educational curricula with international standards and embracing emerging technologies, educational institutions can better equip transportation cadets with the necessary skills and knowledge to succeed in the globalised maritime industry.